Culture Models to Define Key Mediators of Cancer Matrix Remodeling - Fuller, Emily S.; Howell, Viive M. (Frontiers in Oncology, 2014)
High grade serous epithelial ovarian cancer (HG-SOC) is one of the most devastating gynecological cancers affecting women worldwide, with a poor survival rate despite clinical treatment advances. HG-SOC commonly metastasizes within the peritoneal cavity, primarily to the mesothelial cells of the omentum which regulate an extracellular matrix (ECM) rich in collagens type I, III and IV along with laminin, vitronectin and fibronectin. Cancer cells depend on their ability to penetrate and invade secondary tissue sites to spread, however a detailed understanding of the molecular mechanisms underlying these processes remain largely unknown. Given the high metastatic potential of HG-SOC and the associated poor clinical outcome, it is extremely important to identify the pathways and the components of which that are responsible for the progression of this disease. In-vitro methods of recapitulating human disease processes are the critical first step in such investigations. In this context, establishment of an in-vitro ‘tumor-like’ microenvironment, such as 3D culture, to study early disease and metastasis of human HG-SOC is an important and highly insightful method. In recent years many such methods have been established to investigate the adhesion and invasion of human ovarian cancer cell lines. The aim of this review is to summarize recent developments in ovarian cancer culture systems and their use to investigate clinically relevant findings concerning the key players in driving human HG-SOC.